Considerations for the Statistical Visibility of the Trans* Population in the Costa Rican Educational System - Jiménez Asenjo, Wendy (2022)
It is considered that the statistical visibility of the trans* population is necessary for the effective recognition of human rights. Therefore, it is necessary to review the way in which gender variables and indicators are currently constructed and analyze them in the light of some theoretical discussions that should be considered in an effort to contribute to a new proposal that accounts for the gender diversity present in Costa Rican schools. It is concluded that the variable sex (male-female) is still used as part of the ways in which the student body is classified, so it is necessary to have the definition of new variables and indicators that contribute to the design of a policy education aimed at respecting and recognizing a population that has historically been excluded from the system because of their gender identification.